Theoritical Studies of Corossion Inhibition of Coumarin and Coumarin Derivative on Iron by Density Functional Theory Approaches - Ariefin, Mokhamat; Pasaribu, Marvin Horale (Al-Kimia, 2023)
Corrosion of iron is a persistent problem that affects its structural integrity and durability in various industrial applications. The design of effective corrosion inhibitors is crucial for mitigating aluminum corrosion. In recent years, coumarin derivatives have shown promising potential as corrosion inhibitors for iron due to their unique chemical properties. In this research, we employ density functional theory (DFT) calculations to investigate electrochemical parameters of coumarin derivatives on iron corrosion. Coumarin (a) and its derivative: hymechromone (b), esculetin (c), and scopoletin (d) are analyzed using DFT calculation. Some descriptor is used to identify such as ionisation energy (I), electron affinity (A), EHOMO, ELUMO, Egap, electronegativity ( ), hardness ( ), number of fraction electron transferred ( N). Based on the EHOMO, ELUMO, Egap, electronegativity ( ), hardness ( ), the order of inhibitor potential of coumarin and it derivative is c > d > b > a. However, based on the number of fractional electrons transferred ( N), the potential inhibitor of coumarin and it derivative are c > b > d > a.